mTOR Promotes Tissue Factor Expression and Activity in EGFR-Mutant Cancer - Cong, Ying; Li, Qingrou; Zhang, Xuesai; Chen, Yaqing; Yu, Ker (Frontiers in Oncology, 2020)
Mechanistic target of rapamycin (mTOR) signaling pathway mediates the function of oncogenic receptor tyrosine kinases (RTKs). We aimed to elucidate new role of mTOR in EGFR-mutant (EGFR-mut) non-small cell lung cancer (NSCLC) and glioblastoma (GBM) with a focus on tumor microenvironments. Here, we report a novel regulatory link between mTOR complexes (mTORCs) and tissue factor (TF), an initiator of tumor-derived thrombosis. TF is elevated in EGFR-mut NSCLC/GBM cell lines and tumors from patients with poor prognosis. Application of mTORC1/2 inhibitors (AZD8055, WYE-125132, MTI-31, and rapamycin) or genetic mTORC-depletion all reduced TF expression, which appeared to be differentially mediated depending on cellular context. In U87MG and HCC827 cells, mTORC1 exerted a dominant role via promoting TF mRNA transcription. In EGFR-TKI-resistant H1975 and PC9 cells, it was mTORC2 that played a major role in specific repression of lysosomal-targeted TF protein degradation. Successful inhibition of TF expression was demonstrated in AZD8055- or MTI-31-treated H1975 and U87MG tumors in mice, while a TF-targeted antibody antagonized TF activity without reducing TF protein. Both the mTOR- and TF-targeted therapy induced a multifaceted remodeling of tumor microenvironment reflecting not only a diminished hypercoagulopathy state (fibrin level) but also a reduced stromal fibrosis (collagen distribution), compromised vessel density and/or maturity (CD31 and/or α-SMA) as well as a substantially decreased infiltration of immune-suppressive M2-type tumor-associated macrophages (CD206/F4/80 ratio). Thus, our results have identified TF as a functional biomarker of mTOR. Downregulation of mTOR-TF axis activity likely contributes to the therapeutic mechanism of mTORC1/2- and TF-targeted agents in EGFR-mut advanced NSCLC and GBM.